Spontaneous germ line virus infection and retroviral insertional mutagenesis in eighteen transgenic Srev lines of mice. - Spence, S E (1989)
SWR/J-RF/J hybrid mice spontaneously acquire new germ line ecotropic proviruses at high frequency. In the studies described here, we used these hybrids to produce 18 transgenic mouse lines, each carrying a single newly acquired Srev locus (SWR/J-RF/J ecotropic proviral locus). All of the newly acquired proviruses identified in mosaic founder SWR/J-RF/J mice that could be transmitted through the germ line were also present in somatic tissues, demonstrating that viral integration occurred before the germ line was set aside from the somatic lineages. Quantitative analysis of proviral DNA copy numbers in somatic and germinal tissues of mosaic founder parents combined with structural analysis of Srev loci indicated that these proviruses are acquired after multiple rounds of somatic viral reinfection and that most of these viral integration events occurred after DNA replication in the zygote and before DNA replication in the four-cell embryo. The frequency of provirus acquisition in Srev lines that expressed the infectious ecotropic virus was similar to that in SWR.RF mice carrying Emv-16 and Emv-17, suggesting that the chromosomal integration site of the parental locus is not an important determinant for high-frequency provirus acquisition. The frequency of recessive lethal mutations induced by spontaneous viral integration was 5%, which was similar to that induced by preimplantation embryo infection. This approach represents a simple and viable strategy for inducing and studying mutations that affect mammalian development.